Environmental enrichment improves the growth rate, behavioral and physiological response of juveniles of Clarias gariepinus under laboratory conditions - Ojelade, Oluwaseun Christianah; Durosaro, Samuel Olutunde; Akinde, Abiodun O.; Abdulraheem, Ikililu; Oladepo, Mathew B.; Sopein, Comfort A.; Bhadmus, Abiodun S.; Olateju, Mary (Frontiers in Veterinary Science, 2022)
Environmental enrichment (EE) improves the growth rate and welfare of some cultured fishes. However, most cultured fish species are raised in non-enriched housing conditions. Clarias gariepinus is an important commercial fish species, but little is known about the effect of EE on their welfare. This study examined the effect of different EE on the survival rate (SR), growth [mean weight gain (MWG), specific growth rate (SGR) and feed conversion ratio (FCR)], behavioral (feed response, aggressive acts and shoaling time) and physiological responses (blood glucose) of C. gariepinus. One hundred and twenty juveniles of C. gariepinus (31.65 ± 0.69 g) were randomly allocated at 10 fish/tank and subjected to either Plant Enriched (PE), Substratum Enriched (SE), Plant and Substratum Enriched (PSE) and Non-Enriched (NE) tanks in triplicates for 56-days. Behavioral acts were observed for 10 min twice daily, and glucose level in blood samples was evaluated. Data were checked for normality using the Shapiro-Wilk test before being analyzed with the Kruskal-Wallis test. SR and MWG were significantly higher in Clarias gariepinus exposed to SE, with no significant differences among PE, PSE and NE treatments. There was no significant difference between the SGR of PSE and NE. FCR was similar between treatments. The highest condition factor (k) was recorded in SE tanks. Duration of feed response was shorter in SE, but there was no significant difference between the feed response of C. gariepinus exposed to PE and PSE. C. gariepinus exposed to PE, SE and PSE displayed a similar frequency of aggressive acts. African catfish reared in NE (barren) tanks had the least duration of shoaling period. The experiment consistently found the highest and least glucose values in PSE and SE. In conclusion, environmentally enriched housing tanks with SE resulted in the best MWG with a reduced level of aggression in C. gariepinus under laboratory conditions. Thus, EE might be applicable to boost fish productivity on a commercial scale.